Protective effect of a novel hydrogel loaded with CM-UCMSCs on vitrified–thawed ovaries during in vitro culture - Wen, Quan; Zhao, Li; Wang, Ting; Bao, Mingjie; Ling, Yan; Qian, Si; Dou, Yixiao; Lin, Yabin; Wang, Liqun; Dmitrii, Gorbachev; Kurzina, Irina; Zhu, Yuan (Frontiers in Bioengineering and Biotechnology, 2026)
Ovarian tissue cryopreservation and transplantation (OTCT) is an important fertility preservation method for female cancer patients; however, its efficacy is limited by post-transplantation ischemia–reperfusion injury, leading to oxidative stress, apoptosis, and fibrosis that impair ovarian reserve and graft function. Mesenchymal stem cell–conditioned medium shows therapeutic potential through paracrine actions, but clinical use is restricted by relatively limited antioxidant capacity and delivery challenges. To address this, an antioxidant-enriched hydrogel (PG-gel) was developed from N-acetylcysteine–modified gelatin and poly (ethylene glycol) succinimidyl succinate, loaded with conditioned medium from umbilical cord mesenchymal stem cells (CM-UCMSCs). This study evaluated the efficacy of PG-gel in protecting vitrified–thawed ovarian tissue during in vitro culture. The CM-UCMSCs-loaded PG-gel significantly suppressed intracellular reactive oxygen species generation. The PG + CM-UCMSCs group showed markedly reduced follicle loss, improved follicle morphology, decreased collagen deposition, lower apoptosis (fewer TUNEL-positive cells and reduced caspase-3 expression), diminished oxidative damage (lower 8-OHdG), and enhanced glucose consumption compared with the other culture groups. Transcriptomic analysis revealed downregulation of apoptosis-related genes (e.g., Ddit3, Trib3 and Hmox1) and upregulation of mitochondrial metabolism genes (e.g., Mt-atp8, Mt-nd1 and Mt-cyb). In conclusion, the PG + CM-UCMSCs system provided comprehensive protection to cryopreserved ovarian tissue by mitigating oxidative stress, fibrosis, and apoptosis, likely through regulation of apoptotic signaling and enhancement of mitochondrial energy metabolism, thereby offering a promising strategy to improve OTCT outcomes.